Ethnicisation des places publiques en Roumanie. Le cas de la ville de Cluj-Napoca - Coman, Gabriela (Anthropologica, 2022)
Since the collapse of the communist regime (1989), the public spaces of Cluj-Napoca, a multiethnic and multireligious city of mid-western Romania, have become the stage of multiple interventions whose purpose was to produce an ethnic transformation with a Romanian character. These public spaces—central squares—represent the object of my research. The intention of the article is to demonstrate how the central squares’ Romanianization conceals the reformulation process of a social hierarchy and the emergence of new social categories and different instances of public debate. The disputes and the conflicts determined by the authorities’ ethnic interventions revealed the new social stakes and the discourses and actions of different groups.